2020
DOI: 10.1039/d0cc00356e
|View full text |Cite
|
Sign up to set email alerts
|

Aminocarboxylic acids related to aspergillomarasmine A (AMA) and ethylenediamine-N,N′-disuccinic acid (EDDS) are strong zinc-binders and inhibitors of the metallo-beta-lactamase NDM-1

Abstract: Aminocarboxylic acid analogues of aspergillomarasmine A (AMA) and ethylenediamine-N,N′-disuccinic acid (EDDS) were prepared via a robust chemoenzymatic approach. These compounds display potent inhibition of the bacterial resistance enzyme NDM-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(24 reference statements)
2
18
0
Order By: Relevance
“…[30] The K M and K cat values for FC5 hydrolysis by NDM-1 corresponded with those previously found. [31] The results of this study, shown in The ability of inhibitors 1-13 to bind the biologically relevant divalent cations Zn 2+ , Ca 2+ , and Mg 2+ was next investigated. Understanding the metal binding properties of MBL inhibitors is of importance when considering their potential for therapeutic application given the high concentrations of free calcium and magnesium in the bloodstream, with values in adult humans of between 1.17-1.33 mM and 0.6-1.1 mM respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] The K M and K cat values for FC5 hydrolysis by NDM-1 corresponded with those previously found. [31] The results of this study, shown in The ability of inhibitors 1-13 to bind the biologically relevant divalent cations Zn 2+ , Ca 2+ , and Mg 2+ was next investigated. Understanding the metal binding properties of MBL inhibitors is of importance when considering their potential for therapeutic application given the high concentrations of free calcium and magnesium in the bloodstream, with values in adult humans of between 1.17-1.33 mM and 0.6-1.1 mM respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that MBLs of the IMP class are less susceptible to zinc sequestration as a mode of inactivation, while the NDM type are sensitive to strong zinc binders, is in agreement with previous reports. [11,13,31] At present, a mechanistic explanation for this selectivity remains elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Her current research interests include exploring the reactivity of enzymes from natural product biosynthesis pathways for producing pharmaceutically relevant molecules. [16][17][18][19][20][21] Ph, aryl H H RgPAL, AvPAL, PcPAL phenylalanine, β-aryl α-alanines [6,[22][23][24][25][26] chelating compound widely used in industry for a wide range of applications, such as soil remediation, paper manufacturing, waste water treatment and so on. (S,S)-EDDS was isolated as a secondary metabolite from the actinomycete Amycolatopsis japonicum, hypothetically serving as a scavenger of zinc (zincophore) and its bioproduction was strictly repressed by zinc.…”
Section: Properties Structure and Catalytic Mechanismmentioning
confidence: 99%
“…In addition, a series of aminocarboxylic acid analogues of (S,S)-EDDS was synthesized by the addition of various diamine substrates to fumaric acid catalyzed by EDDS lyase. [21] The enzyme was shown to accept various (substituted) diamines with two to four atoms between the two amino groups, giving good conversions (47-83 %) and yielding the corresponding aminocarboxylic acid products ( Figure 5) with moderate to good isolated yield. Like AMA, AMB and their derivatives, (S,S)-EDDS and several of its analogues demonstrated effective inhibition of the bacterial metallo-β-lactamase NDM-1, displaying a strong correlation between the inhibitory potency of the compounds and their ability to bind zinc.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation